Diagnostic dilemma of celiac disease presenting with weight loss and secondary amenorrhea: A case report. Issue 42 (21st October 2022) - Mumtaz, Arif; Khan, Qaisar Ali; Asim, Nowshad; Baqi, Abdul; Iram, Sumaira; Majeed, Abdul; Tahir, Muhammad Junaid; Islam, Md. Saiful; Yousaf, Zohaib
Abstract : Rationale: Celiac disease (CD) is autoimmune enteropathy affecting the proximal small intestinal mucosa. It is caused by insensitivity to gluten, a protein predominantly presented in wheat. CD is classically associated with gastrointestinal symptoms. The non-classic clinical presentation of CD can present with other organ involvement. Non-human leukocyte antigens genes are associated with atypical forms. Patients concern: We reported a case of 30-year-old female who presented with progressive pallor, amenorrhea, and unexplained weight loss with generalized body weakness. Her body mass index was 20. The patient was having no other systemic manifestations. Diagnosis: This paper reports a case of a female patient having CD without its typical features. Her laboratory evaluation revealed microcytic anemia. Anti-TTg IgA and Anti-TTG IgG antibodies were raised, ferritin and folate were low, and there was mild hyperbilirubinemia. However, follicle-stimulating hormone, luteinizing hormone, and serum estradiol levels were normal. She was diagnosed with a case of anemia resulting from malabsorption caused by CD. Interventions: A management plan was devised based on a strict gluten-free diet. The patient received supplements containing folates, iron, calcium, zinc, and vitamins A, D, E, B6, and B12. Outcomes: After 3 months of treatment with strict gluten-free diet patient showed remarkable improvement. Her hemoglobin level raised with weight gain. Her normal menstrual cycle was restored with complete resolution of symptoms at 1 year follow-up. Lessons: The pathogenesis of the atypical CD is multifactorial, but impaired uptake of micronutrients from the duodenum is the most likely cause, even if other common features of classical forms, such as bloating and diarrhea, are absent. Lack of awareness about atypical forms may lead to under-diagnoses of the disease. The physicians should consider the atypical presentations of CD to avoid the under-diagnoses of this multisystem disorder.